2018
DOI: 10.11648/j.ajtab.20180403.12
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Influence of Sustainability Knowledge and Orientation to Slow Consumption on Fashion Leaders’ Drivers of Fast Fashion Avoidance

Abstract: This research explores the complex relationship between fashion leaders' motivations toward slow vs. fast fashion, and proposing that all consumers have the potential to adopt more sustainable consumption behaviors, offers suggestions for sustainable companies aiming to better understand and target these consumers. Fashion leaders are particularly susceptible to overconsumption, yet they are also the most attuned to fashion industry information (e.g., sustainability) and influence others through their tastes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…However, the study in Spain found that overly trendy style is reflected in the symbolic style with inauthenticity, and that irresponsibility is formed independently as a dimension of moral avoidance belief. Cavender and Lee [70] studied the US consumers' fast fashion avoidance and suggested that foreignness was not a sub-dimension of avoidance beliefs, but that localism as the orientation of slow consumption can influence fast fashion avoidance beliefs. The findings imply that negative beliefs about fast fashion are due to the evaluation of the fast fashion brand's products and services as well as the invasion of individual identity in the process of fashion diffusion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the study in Spain found that overly trendy style is reflected in the symbolic style with inauthenticity, and that irresponsibility is formed independently as a dimension of moral avoidance belief. Cavender and Lee [70] studied the US consumers' fast fashion avoidance and suggested that foreignness was not a sub-dimension of avoidance beliefs, but that localism as the orientation of slow consumption can influence fast fashion avoidance beliefs. The findings imply that negative beliefs about fast fashion are due to the evaluation of the fast fashion brand's products and services as well as the invasion of individual identity in the process of fashion diffusion.…”
Section: Discussionmentioning
confidence: 99%
“…Kim et al [25] suggested and confirmed the conceptual structure of fast fashion avoidance beliefs and we reconfirmed and showed its satisfactory validity and reliability in Korea and Spain. Cavender and Lee [70] also identified fast fashion avoidance beliefs based on Kim et al's structure [25] in the US. This study's findings also revealed that the conceptual structure and its sub-dimensions of fast fashion avoidance beliefs can differ based on the growth stage of fast fashion and consumers' accumulated experience.…”
Section: Theoretical and Managerial Implicationsmentioning
confidence: 95%
See 1 more Smart Citation
“…The author concluded that the consumers are not willing to pay for that kind of products about which they are less aware of and have never seen any advertisement. Lack of awareness/advertisements regarding sustainable electronic product among the consumers reduces the probability of further purchase/usage (Wheale and Hinton, 2007;Biel and Dahlstrand, 2005;Young et al, 2010;Annunziata and Mariani, 2018;Cavender and Lee, 2018). Thus, the lack of awareness/advertisement is also a significant barrier of sustainable consumer behaviour.…”
Section: Subjective Norm Barriersmentioning
confidence: 99%
“…Cavender and Lee (2018a; 2018b) introduced the concepts of industry responsibility and consumer responsibility as two distinct aspects of socially responsible consumption and disposal. Apparel production relates to industry responsibility while apparel consumption attaches to consumer responsibility (Cavender et al, 2018a;2018b). On the industry side, high levels of production have exacerbated the negative environmental (e.g., natural resource depletion) and social (e.g., working conditions) impacts of the clothing industry.…”
mentioning
confidence: 99%